The Use of Kilroy Spring for Eruption of Palatally Impacted Canines and Its Long-Term Follow-Up - Ali Onkan Peynirci; Gökhan Önçağ (Galenos Yayinevi, 2011)
In this study treatment of a impacted teeth case using Kilroy Spring and its long term follow-up is presented.